Mediterranean Shrubs: Natural Anthelmintics in the Diet Selected by Grazing Goats - Padre, Ludovina (2020)
L. Padre1, C. Costa1, C.C. Belo2, J. P. Barbas2, S. Cavaco-Gonçalves2, J. M. B. Ribeiro2, A. T. Belo2 1ICAAM – Department of Veterinary Medicine, School of Science and Technology, Évora University, Póloda Mitra, Ap. 94, 7006-554 Évora 2INIAV – Santarém – NationalInstituteof Agrarian and Veterinarian Research, Quinta da Fonte Boa, 2005-048 Vale de Santarém The project VegMedCabras aims to promote ecological and sustainable grazing of Mediterraneanshrub vegetation by goats. These animals with very selective feeding behavior, tend to actively seek out the most nutritive parts of woody plants, showing adaptations to the chemical defenses of this kind of vegetation. At the same time, goats have a higher sensitivity to gastrointestinal strongyles (GIS) infection compared to other ruminants. In order to control parasitic infection, the use of synthetic anthelmintics is recurrent, resulting in increased resistance to treatments associated with environmental contamination and residues in the final product. Several authors [1,2] have verified that bioactive compounds present in the shrub vegetation are a promising solution in the control of the gastrointestinal strongylosis. The objectives of the project are to document the species selected by browsing goats, evaluate their nutraceutical value (nutritionalvalue and anthelmintic potential), to promote the animals’ productive efficiency, the sustainabilityof the farms, the biodiversityof the environment as well as the control of combustible vegetation. Twenty-six non-producing Charnequeira breed goats were used, having access to a shrub area and a drylandpasture. Goats were grouped according to the length of exposure to the shrub area. Natural GIS infections were evaluatedindividuallyfor egg elimination levels prior to the start of the test and monthlythereafter.Health status of the animals was evaluatedthrough the microhematocrit and total plasma protein. Browsing/grazing goats were observed on separate occasions and shrubs were sampled to evaluate the nutraceutical value of the selected diets. The preference of the goats for Olea europaea var. sylvestris and Rhamnus lycioides was evident. With these shrubs decreased availability, goats increased the demand for other species, namely Pistacia lentiscus and Quercus coccifera. The results obtainedin the evaluation of the parasitic infection indicate a relationshipbetween the decrease on GIS elimination levels and broesing the shrub vegetation. Also, after a grazing period of about 6 months, the biomass reduction was striking. Keywords: goats; mediterranean shrubs; natural anthelmintics; gastrointestinal strongyles; sustainable production; nutraceiticalplants This work is funded by the project VegMedCabras - Mediterranean shrubs: natural anthelminticsin the diet selected by grazing goats (ALT20-03-0145-FEDER-000009) co-financed by ALENTEJO2020 program-European Regional Development Fund.